Dynamic response of a 190m-high transmission tower for a large river crossing. Issue 4 (18th May 2016) - Fadel Miguel, Leandro Fleck; Kaminski, João; Miguel, Letícia Fleck Fadel; Riera, Jorge Daniel; Menezes, Ruy Carlos Ramos de
Abstract: The construction of a double circuit 500 kV transmission line (TL) in the Brazilian Amazon region is currently in progress. In addition to its length within the rain forest, the TL had to overcome large river crossings and environ- mental constrains. Among them, the crossing of the Trombetas River is one of the most important, with a total length of more than 5100 m. The proposed design includes two 190 m high towers necessary to attain spans as long as 1600 m. Additionally, the towers had to be supported by concrete columns, 10 m above ground level, due to the annual flood- ing of the river bed. These structures demand a detailed assessment, since the design required long-span conductors and tall structures that are outside the range normally considered in codes. In this context, the present article describes the dynamic analysis of the complete TL segment for this crossing, with emphasis on the response of the 190 m-high main structure which is subjected to Extended Pressure Systems and Thunderstorm wind loads, as well as cable rupture. The entire TL crossing is modelled, including the two highest towers and all other elements. The responses determined by such approach are then compared to values obtained by standard practice.